UPR Induction Prevents Iron Accumulation and Oligodendrocyte Loss in ex vivo Cultured Hippocampal Slices - Healy, Sinead; McMahon, Jill; FitzGerald, Una (Frontiers in Neuroscience, 2018)
The accumulation of iron within the brain occurs in many chronic disorders including Alzheimer’s and Parkinson’s disease and multiple sclerosis. Outside the CNS, a link between levels of iron and the unfolded protein response has already been established. To determine if such a relationship operates in within the brain, we used our ex vivo hippocampal slice-based model of iron accumulation. Ferrocene addition caused accumulation of iron within slices and loss of oligodendrocytes, an effect that was partially inhibited when ferrocene and ER stressor tunicamycin (Tm) were added together. An upward trend (not found to be statistically significant) in the expression of UPR transcripts in response to ferrocene was demonstrated using real-time PCR, while a significant upregulation of mRNA for B cell immunoglobulin-binding protein (BiP) and C/EBP homologous binding protein (CHOP) occurred following exposure to Tm. In silico analysis revealed consensus DNA-binding sequences for UPR-associated transcription factors within the promoter regions of eight iron-regulatory genes. In addition, dual-staining for CHOP and oligodendrocyte transcription factor 2 (OLIG2) or Ionized calcium binding adaptor molecule 1 (Iba1) showed nuclear expression of CHOP in some oligodendrocyte-lineage cells in response to Tm or Tm+ferrocene, but CHOP was rarely found in microglia. Co-expression of UPR-associated activated transcription factor 6 (ATF6) was detected in the nuclei of some oligodendrocyte-lineage cells exposed to Tm alone, or to Tm and ferrocene, but rarely in microglia. These data highlight the therapeutic potential of targeting UPR-associated proteins when developing novel treatments for chronic brain disorders that are affected by dysregulated iron.